Learning strategies evaluation in students with attention deficit hyperactivity disorder - Capellini, Simone Aparecida [UNESP]; Oliveira, Adriana Marques de [UNESP] (My University, 2013)
This study aim to verify the use of learning strategies in students of the elementary level presenting interdisciplinary diagnosis of attention dei cit hyperactivity disorder (ADHD). Nine students, male gender, attending 3rd to 9th grade level of the elementary level, average age 10 years and 7 months, presenting interdisciplinary diagnosis of attention dei cit hyperactivity disorder (ADHD). h e students were submitted to the application of the Evaluation of Learning Strategies from elementary level – EAVAP-EF – scale, which aimed to evaluate the strategies reported and used by students in situation of study and learning, as follows: cognitive strategies, metacognitive strategies and absence of dysfunctional metacognitive strategies. h e general result at EAVAP-EF scale, showed that students with ADHD reached the percentile 25%, considered as low performance in the use of the learning strategies. For the variable absence of dysfunctional metacognitive strategies, the students presented percentile 30%, percentile 25% for cognitive strategies and 55% for metacognitive strategies. h e results showed that ADHD students do not use ef ectively the learning cognitive and metacognitive strategies and present the use of dysfunctional metacognitive strategies. h ese alterations match with the framework of ADHD because the entry of information, either visual or auditory, showed alterations, derived from inattention, which af ected the learning in classroom situation.

Questo studio ha come obiettivo quello di verii care l’uso di strategie di apprendimento negli alunni di scuola primaria con diagnosi multidisciplinare di Disturbo di Attenzione ed Iperattività (ADHD). L’articolo presenta il campione, gli strumenti utilizzati per la valutazione cognitiva e metacognitiva e i risultati signii cativi per la comprensione dei processi di insegnamento-apprendimento in classe.
Keywords: Learning; learning strategies; Attention Deficit with Hyperactivity Disorder